BUSY BOOK MEDIA DEVELOPMENT TO STIMULATE LITERACY AND NUMERACY DEVELOPMENT ASPECTS EARLY CHILDHOOD - Nur Ifyati; Mohammad Syahri; Siti Fatimah Soenaryo (Universitas Islam Negeri Mataram, 2025)
This study aims to develop busy book media to stimulate aspects of literacy and numeracy development in early childhood. The research method used is Research and Development (R&D) with the ADDIE model consisting of analysis, design, development, implementation, and evaluation. This research and development were carried out through 3 stages of trials, namely material expert trials, media expert trials, and trials of media use in children. The subjects of the research and development were 25 children in group A, aged 4-5 years at TK ABA Karangasem 03 Jetak Paciran. Data collection techniques and instruments used included material expert questionnaires, media expert questionnaires, children's response questionnaires, interview and observation sheets, and documentation. The data analysis technique in this study used qualitative and quantitative data analysis. The results of this research and development showed that the value obtained by the busy book media from the material expert trial was 82% in the